Dramatic response of cutaneous, nail, and joint symptoms of psoriasis to apremilast - Meghana Bathina; Amina Asfiya Iqbal; Malcolm Pinto; Manjunath M Shenoy (Wolters Kluwer Medknow Publications, 2019)
Apremilast has been available in India for the past 6 months as a therapy for psoriasis. A 31-year-old male patient with a diagnosis of psoriasis with oligoarthritis who was not tolerating methotrexate was treated with apremilast. We noticed a dramatic response to the cutaneous and joint symptom within a month of initiation of the therapy. We also noticed improvement in the nail changes. He tolerated the drug except for an episode of diarrhea that resolved without any intervention. Apremilast is a useful addition to the therapeutic armamentarium of psoriasis and arthritis.